Synthesis conceptual framework of Supply Chain Business Intelligence for Educational Management in Thai Higher Education Institutions - Artaphon Chansamut (International Journal of Supply Chain Management, 2021)
This objective of paper were to synthesis and evaluate a conceptual framework of Supply Chain business intelligence for educational management in Thai higher education institutions. The research methodology consists of Review documentation and literature, Create preliminary conceptual framework, Propose conceptual framework, Analyze the output data .The samples are fiveteen experts selected by purposive sampling. The data is analysed by means and standardized deviations . The results of synthesis conceptual framework of supply chain Business Intelligence for Educational Management in Thai Higher Education Institutions find that, It were five components: main component and Minor ingredients namely Suppliers, University manufacture, Customers and Consumer.A conceptual framework of assessment system using Back-Box technique. The overall evaluation result synthesis conceptual framework of supply chain Business Intelligence for Educational Management in Thai Higher Education Institutions, shows the overall rating mean of 3.58 suggesting that The framework aims to support sustainable business intelligence development.